RPL10L Is Required for Male Meiotic Division by Compensating for RPL10 during Meiotic Sex Chromosome Inactivation in Mice - Jiang, Long; Li, Tao; Zhang, Xingxia; Zhang, Beibei; Yu, Changping; Li, Yang; Fan, Suixing; Jiang, Xiaohua; Khan, Teka; Hao, Qiaomei; Xu, Peng; Nadano, Daita; et al. (Current biology, 2017)
The mammalian sex chromosomes have undergone profound changes during their evolution from an ancestral pair of autosomes [1–4]. Specifically, the X chromosome has acquired a paradoxical sex-biased function by redistributing gene contents [5, 6] and has generated a disproportionately high number of retrogenes that are located on autosomes and exhibit male-biased expression patterns [6]. Several selection-based models have been proposed to explain this phenomenon, including a model of sexual antagonism driving X inactivation (SAXI) [6–8] and a compensatory mechanism based on meiotic sex chromosome inactivation (MSCI) [6, 8–11]. However, experimental evidence correlating the function of X-chromosome-derived autosomal retrogenes with evolutionary forces remains limited [12–17]. Here, we show that the deficiency of Rpl10l, a murine autosomal retrogene of Rpl10 with testis-specific expression, disturbs ribosome biogenesis in late-prophase spermatocytes and prohibits the transition from prophase into metaphase of the first meiotic division, resulting in male infertility. Rpl10l expression compensates for the lack of Rpl10, which exhibits a broad expression pattern but is subject to MSCI during spermatogenesis. Importantly, ectopic expression of RPL10L prevents the death of cultured RPL10-deficient somatic cells, and Rpl10l-promoter-driven transgenic expression of Rpl10 in spermatocytes restores spermatogenesis and fertility in Rpl10l-deficient mice. Our results demonstrate that Rpl10l plays an essential role during the meiotic stage of spermatogenesis by compensating for MSCI-mediated transcriptional silencing of Rpl10. These data provide direct evidence for the compensatory hypothesis and add novel insight into the evolution of X-chromosome-derived autosomal retrogenes and their role in male fertility. •Rpl10l is essential for the transition from prophase to metaphase in male meiosis I•Rpl10l expression compensates for Rpl10 silencing resulting from MSCI•Ectopically expressed RPL10L can substitute for RPL10 in cultured somatic cells•Rpl10 transgenic expression restores spermatogenesis and fertility of Rpl10l−/− males Jiang et al. show that RPL10L is required for the transition from prophase to metaphase in male meiosis I by compensating for RPL10 inactivation resulting from MSCI. The authors provide direct evidence for an X-to-autosome retrogene compensatory hypothesis and novel insight into the functions of these retrogenes in spermatogenesis.